Določitev višinske transformacijske ploskve na območju vzhodne Slovenije (= Determination of the height transformation surface in an area of eastern Slovenia) - Božo Koler; Tilen Urbančič; Žiga Kobale (Geodetski Vestnik, 2022)
In this work, we analyzed the quality of height transformation between the old height system SVS2000 (vertical datum Trieste) and the new height system SVS2010 (vertical datum Koper). Based on the height differences of the benchmarks between the old and the new height systems stabilised in the area of eastern Slovenia, we determined the height transformation surface for two areas of different sizes. For both areas we analyzed the influence of different interpolation methods and the influence of using height differences of benchmarks of different orders of the levelling net. We found that the quality of height transformation is satisfactory for most surveying services. We have also analyzed the quality of the height transformation based on the average height difference of the benchmarks by using the SiVis software, which is intended for the transformation of ellipsoidal heights obtained by GNSS measurements, between the old and the new height systems.